Proceedings of the 1st International Conference on Advanced Multidisciplinary Research (ICAMR 2018) 2019
DOI: 10.2991/icamr-18.2019.69
|View full text |Cite
|
Sign up to set email alerts
|

Open Inquiry with Learning Journal Promoting Metacognitive Skills and Retention of Students with Low Academic Achievements

Abstract: The expected skill to face the 21st century is the level of thinking that involves high order thinking concept known as metacognition, which is also believed as a notable predictor on retention. The purpose of this study is to investigate the effect of open inquiry model combined with a learning journal on metacognitive skills and retention of students with low and high learning achievement levels. This study was quasi-experimental research, using the equivalent post-test only with control group design. The su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…LA children require special attention and different learning approach compared to those are average and excellent student or children. Learning material also should be provided according to their need as most of them also have literacy problem as well as oral communication skill [7].…”
Section: Low Achieving Childrenmentioning
confidence: 99%
“…LA children require special attention and different learning approach compared to those are average and excellent student or children. Learning material also should be provided according to their need as most of them also have literacy problem as well as oral communication skill [7].…”
Section: Low Achieving Childrenmentioning
confidence: 99%
“…The results of previous studies indicated that the guided in quiry model was more effective at increasing learning outcomes compared to conventional learning (Nurmayani et al, 2018;. Applying a laboratory-based guided inquiry model involves students to actively seek and find solutions to the questions given (Rahmat et al, 2019). Th e inquiry model can also train studen ts' science process skills .…”
Section: Introductionmentioning
confidence: 99%